Specific traits of communal berths in ports open to public transport in Primorje-Gorski Kotar County - Legac, Lora (Array, 2020)
Primorje-Gorski Kotar County has eight county port authorities operating since 1999, which manage a total of 101 ports open for public transport, 27 of which are of county importance and 74 ports are of local importance. The focus of this article is directed on county ports communal areas open for public transport, i.e. on communal berths in such ports. The article processes a number of communal berths managed by each county port authority in Primorje-Gorski Kotar County, including the amount of compensation for such moorings. The number of requests for communal berths for each of the eight county port authorities was collected by field research to compare the current capacity with the required capacity of communal moorings. The problems which occur during the use of communal berths and possible solutions to those problems will also be presented in the article.